The Kenya National Domestic Biogas Programme: can carbon financing promote sustainable agriculture? - Porras, Ina; Vorley, Bill; Amrein, Alexandra (2015)
The Kenya National Domestic Biogas Programme promotes the installation of biodigesters in agricultural smallholdings across the country. Biogas provides on-demand energy in the home and is demonstrably better for the environment as it reduces dependence on firewood, and better for health as a smokeless fuel. It also qualifies for payments for ecosystem services (PES) in the form of carbon offsets. Can carbon finance therefore play a role in upscaling the biogas industry to allow more, and poorer, households to participate? Or are the returns too low, especially given the transaction costs involved? And how can farmers benefit directly? This report examines the value chains and business models involved in the biogas programme to see what contribution carbon finance can make – if any – to growing Kenya’s domestic biogas industry.